2016
DOI: 10.1002/eat.22604
|View full text |Cite
|
Sign up to set email alerts
|

Appearance evaluation of others' faces and bodies in anorexia nervosa and body dysmorphic disorder

Abstract: Objective Individuals with anorexia nervosa (AN) and body dysmorphic disorder (BDD) exhibit distorted perception and negative evaluations of their own appearance; however, little is known about how they perceive others’ appearance, and whether or not the conditions share perceptual distortions. Method Thirty participants with BDD, 22 with AN, now weight-restored, and 39 healthy controls (HC) rated photographs of others’ faces and bodies on attractiveness, how overweight or underweight they were, and how much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
(148 reference statements)
1
20
1
1
Order By: Relevance
“…This explanation, however, implies that patients with AN should also overestimate the weight of other thin people. Interestingly, some recent studies observed that patients with AN indeed tend to overestimate other people's weight when rating their weight in categories (Horndasch et al 2015 ; Moody et al 2016 ). In contrast, another study observed that participants with AN accurately memorized and adjusted another person's body (Øverås et al 2014 ).…”
mentioning
confidence: 99%
“…This explanation, however, implies that patients with AN should also overestimate the weight of other thin people. Interestingly, some recent studies observed that patients with AN indeed tend to overestimate other people's weight when rating their weight in categories (Horndasch et al 2015 ; Moody et al 2016 ). In contrast, another study observed that participants with AN accurately memorized and adjusted another person's body (Øverås et al 2014 ).…”
mentioning
confidence: 99%
“…Participants engaged in a task of matching photos of bodies or shapes in the MR scanner. The photos were black and white photos of other people's bodies (female and male subjects) wearing underwear, ranging from normal to overweight (Moody et al, 2017).…”
Section: Figure and Table Legendsmentioning
confidence: 99%
“…To replicate and extend present research, we assume that females with a diagnosis of an ED show larger IPD as compared to control participants without EDs (H1), that eating psychopathology assessed with the EDI‐2, body‐image‐related behaviors assessed with the BCAQ and BMI of the person itself would be positively related to overall IPD (H2). We further expect that normal and ideal‐weighted avatars produce the smallest IPDs as compared to fat and underweight avatars (H3); these effects may be particularly attenuated in EDs (Moody et al, ), as body weight is a salient emotional cues for individuals with EDs (H4). Finally, we hypothesized that women with high levels of body‐image avoidance prefer relatively larger IPDs towards fat as compared to normal avatars, indicating stronger avoidance tendencies based on alleviated body weight (H5).…”
Section: Introductionmentioning
confidence: 99%